Effects of Astaxanthin supplementation on selected metabolic parameters, anthropometric indices, Sirtuin1 and TNF-α levels in patients with coronary artery disease: A randomized, double-blind, placebo-controlled clinical trial - Heidari, Marzieh; Chaboksafar, Maryam; Alizadeh, Mohammad; Sohrabi, Bahram; Kheirouri, Sorayya (Frontiers in Nutrition, 2023)
Background: Atherosclerosis can develop as a result of an increase in oxidative stress and concurrently rising levels of inflammation. Astaxanthin (AX), a red fat-soluble pigment classified as a xanthophyll, may be able to prevent the vascular damage induced by free radicals and the activation of inflammatory signaling pathways. The objective of the current study is to assess the effects of AX supplementation on cardiometabolic risk factors in individuals with coronary artery disease (CAD). Methods: This randomized double-blind placebo-controlled clinical trial was conducted among 50 CAD patients. Participants were randomly allocated into two groups to intake either AX supplements (12mg/day) or placebo for 8 weeks. Lipid profile, glycemic parameters, anthropometric indices, body composition, Siruin1 and TNF-α levels were measured at baseline and after 8 weeks. Results: Body composition, glycemic indices, serum levels of TNF-α, Sirtuin1 did not differ substantially between the AX and placebo groups (p>0.05). The data of AX group showed significant reduction in total cholesterol (−14.95 ± 33.57 mg/dl, P < 0.05) and LDL-C (−14.64 ± 28.27 mg/dl, P<0.05). However, TG and HDL-C levels could not be affected through AX supplementation. Conclusion: Our results suggest that AX supplementation play a beneficial role in reducing some components of lipid profile levels. However, further clinical investigations in CAD patients are required to obtain more conclusive findings. Keywords: coronary artery disease, astaxanthin, lipid profile, glycemic indices, inflammation